(untitled) (Superficies y Vacío, 2013)
Fabrication of titanium dioxide (TiO2) nanostructured porous layers is reported in this work, via electrochemical anodization in a low potential range (1V vs. Ecorr - 3V vs. Ecorr), from titanium foils immersed in an aqueous electrolyte (CH3COOH /HF). This type of nanoscale structures have caused great interest in recent years because of the high expectations that have been established for nanomaterials applications, mainly concerning solar energy and gas sensing. The morphology of the resulting fi lms was analysed by scanning electron microscopy (SEM). Layer thickness, pore arrangement and pore diameter were found to be strongly dependent on the anodizing time and on the initial morphology of the titanium surface. Current density evolution for this process was registered, yielding similar curves to those reported in literature at higher potentials. The application of low potentials, though economically convenient, imposes a restriction on the optimization possibilities for the process. Such a restriction is intended to be offset with an adjustment in electrochemical and mechanical pretreatments in order to achieve a higher ordering degree of nanopores, for what further research will be required.